Smoking and Poverty: Empirical Study of Districts and Cities in Indonesia - Aditya, Toni; Yuniarti, Dini; Abdulkarim, Fatima Muhammad (Universitas Ahmad Dahlan, Yogyakarta, 2025)
The purpose of this study is to examine the factors that influence poverty in cities and districts in Indonesia. Using a case study of 514 cities and districts in Indonesia from 2018 to 2021, this study examines the effect of cigarettes and other factors on poverty in the country. The dependent variable in this study is the poverty rate, and the independent variables are as follows: cigarettes consumption, GRDP, average years of male schooling (RLSL) and average years of female schooling (RLSP). This study uses a panel data method which is a combination of time series and cross section, and is a type of quantitative research. The fixed effect model is the most appropriate model to adopt, according to the research findings. The research findings show that partially cigarettes have a significant positive effect on poverty. Meanwhile, Gross Regional Domestic Product (GRDP), Average Years of Male Schooling (RLSL), and Average Years of Female Schooling (RLSP) do not affect poverty but tend to be positive. Simultaneously, the variables in the study, namely cigarettes, GRDP, IHPB, and IHPB together have a significant effect on poverty. Cigarettes absorb a large portion of household income that should be allocated to basic needs such as food, education, and health. As a result, household spending on basic needs is often reduced, which can reduce the quality of life and hinder opportunities to escape poverty. This can worsen poverty by reducing the allocation of funds for investment in basic needs and improving long-term welfare.